NGAL is a Novel Target in Hypertension by Modulating the NCC-Mediated Renal Na Balance - Bonnard, Benjamin; El Moghrabi, Soumaya; Ueda, Kohei; Lattenist, Lionel; Soulie, Matthieu; López-Andrés, Natalia; Xhaard, Constance; Shimosawa, Tatsuo; Rossignol, Patrick; Jaisser, Frédéric (Hypertension (Dallas, Tex. 1979), 2023)
The expression of NGAL/lcn2 (neutrophil gelatinase-associated lipocalin) is directly modulated by mineralocorticoid receptor activation but its role in blood pressure control is unclear. a potential relationship between NGAL plasma levels, systolic blood pressure and urinary Na excretion was assessed in the STANISLAS cohort. The specific role of NGAL/lcn2 in salt-sensitive hypertension was studied using lcn2-knockout mice (lcn2 KO) fed with low-Na diet (0Na). we show that NGAL plasma levels positively correlate with systolic blood pressure, whereas they negatively correlate with urinary Na excretion in subjects of the STANISLAS cohort. Prolonged feeding of lcn2 KO mice with a 0Na diet induced lower systolic blood pressure than that of the control group (wildtype), suggesting a role for NGAL/lcn2 in Na-balance homeostasis. Short-term or prolonged 0Na increased Na-Cl cotransporter (NCC) phosphorylation in the cortex of wildtype mice, which was prevented in lcn2 KO mice. Recombinant mouse lcn2 injections in lcn2 KO mice induced NCC phosphorylation in the kidney cortex, associated with decreased urinary Na excretion. Ex vivo experiments using kidney slices from lcn2 KO mice showed increased NCC phosphorylation by recombinant murine lcn2. In addition, recombinant murine lcn2 induced activation of CamK2β (calcium/calmodulin-dependent protein kinase II β subunit) phosphorylation in lcn2 KO mice and in kidney slices, providing an underlying mechanism involved in lcn2-induced NCC phosphorylation. Indeed, the inhibition of CamK2β prevented NCC phosphorylation induced by recombinant lcn2 in kidney slices. we highlight a novel role of NGAL/lcn2 as a modulator of the activity of the renal sodium transporter NCC affecting salt-sensitive blood pressure.